Traditional Chinese Medicine nursing of a patient with lymphoedema of the lower limbs after radical hysterectomy for cervical cancer (1例宫颈癌术后双下肢淋巴水肿患者的中医特色护理体会) - SU Heng (苏恒); WANG Xiaoyin (王潇寅); CHEN Lei (陈蕾); ZHANG Hanlu (张涵璐); SU Shuzhen (苏书贞) (Association of Integrative Nursing, 2024)
This paper summarized the traditional Chinese Medicine nursing measures for a patient with lymphoedema of the lower limbs after radical hysterectomy for cervical cancer. Nurses had taken the comprehensive risk assessment, medication guidance and other routine nursing interventions. Based on the syndrome differentiation, Traditional Chinese Medicine nursing techniques including acupoint application, collateral-pricking and cupping treatment, in combination with interventions of improving microcirculation of limb tissues and skin hygiene, were carried out to relieve the edema of the lower limbs and improve the activity of daily living. (本文总结1例宫颈癌术后双下肢淋巴水肿患者的中医特色护理经验。基于辨证分型, 在完善护理评估、用药指导等常规护理的基础上, 采用穴位贴敷、刺络拔罐等中医特色护理措施, , 积极改善微循环, 加强皮肤护理, 减轻患者水肿程度, 促进患者日常活动能力恢复。)